Investigation of thoracic spine kinematics in adult sports participants with chronic groin pain during a single leg drop landing task - Morris, Tracy Louise (Stellenbosch : Stellenbosch University, 2014)
Thesis (MScPhysio)--Stellenbosch University, 2014.